2018
DOI: 10.1029/2018ja025695
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Two Flapping Types of Magnetotail Current Sheet: Implication for the Flapping Mechanism

Abstract: Flapping motion of the current sheets of planetary magnetotails is a common dynamic phenomenon. Previous studies of the Earth's magnetotail suggest that its flapping motion has two forms, that is, kink‐like flapping that can propagate as waves toward both flanks and steady flapping that moves up and down but does not propagate. Although some models have been proposed to explain the kink‐like flapping, its mechanism remains unclear. This paper surveys 87 flapping events statistically with respect to their flapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…Therefore, it is possible for a spacecraft dawnward of TC‐1 to observe a dawnward propagating flapping on the dusk side of the plasma sheet, as shown in Figure 2a. The dawnward (duskward) propagation of dusk side (dawn side) flapping events has been reported in previous studies (Gao et al, 2018; Sergeev et al, 2003), although they have not been commonly observed.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, it is possible for a spacecraft dawnward of TC‐1 to observe a dawnward propagating flapping on the dusk side of the plasma sheet, as shown in Figure 2a. The dawnward (duskward) propagation of dusk side (dawn side) flapping events has been reported in previous studies (Gao et al, 2018; Sergeev et al, 2003), although they have not been commonly observed.…”
Section: Discussionsupporting
confidence: 58%
“…Wu et al (2016) suggested that nonpropagation steady current sheet flapping likely occurred due to the instability caused by the ion temperature anisotropy in the diffusion region of the reconnection. Gao et al (2018) indicated that the up‐down motion of a current sheet around midnight could induce a kink‐like flapping motion that propagated toward both flanks. The back‐and‐forth crossings of a plasma sheet have been observed to be induced by the sudden impulse (SI) of solar wind (Keika et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The position of the tail neutral sheet is often subjected to dynamical motion in the north-south Z direction termed as flapping (e.g., Speiser and Ness 1967;Lui et al 1978;Sergeev et al 1998Sergeev et al , 2004Zhang et al 2002Zhang et al , 2005Gao et al 2018). In general, the position of the neutral sheet is affected by three major causes: hinging, warping and twisting (or rotation) (Tsyganenko et al 1998;Tsyganenko and Fairfield 2004;Tsyganenko et al 2015;Xiao et al 2016, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The oscillatory (or flapping) motion of Earth's cross-tail current sheet has been extensively studied by various missions, such as THEMIS (Sun et al, 2014) and Cluster (Gao et al, 2018;Rong et al, 2015Rong et al, , 2018Runov et al, 2005;Sergeev et al, 2003;Sun et al, 2010;Zhang et al, 2002), and is commonly identified in the magnetic field measurements as multiple reversals of the x component of the magnetic field B X (i.e., multiple crossings of the current sheet) (Speiser & Ness, 1967). Note: The Geocentric Solar Magnetospheric (GSM) coordinate system is commonly used in these Earth studies where the x axis points toward the Sun along the Sun-Earth line, the z axis is the projection of the Earth's dipole axis onto the plane perpendicular to the x axis, and the y axis completes the right-handed system.…”
Section: Introductionmentioning
confidence: 99%